Environment-friendly material capable of resisting drought, retaining water, releasing nitrogen and removing cadmium and lead as well as preparation method and application of environment-friendly material

By reacting solid waste and diatomaceous earth to prepare hydrated calcium silicate, and combining it with peel powder and other materials, an environmentally friendly material that can repair heavy metal pollution in the soil and provide long-term fertilization for plants is prepared, which solves the dual problems of heavy metal pollution in the soil and plant fertilization, and achieves efficient heavy metal adsorption and slow-release fertilizer effects.

CN119685027APending Publication Date: 2025-03-25SICHUAN CHUANJIAO ROAD & BRIDGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848935.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Soil heavy metal pollution is severe, and there is a lack of a material that can repair heavy metal pollution in the soil while ensuring long-term fertilization of plants.

Method used

Hydrated calcium silicate is prepared by mixing solid waste, diatomaceous earth and water, and reacting with waste peel powder, monomer acid and crosslinking agent to prepare an environmentally friendly material that is drought-resistant, water-retaining, nitrogen-release and cadmium-lead removal.

Benefits of technology

This material has excellent three-dimensional structure thermal stability, hydrophilic group content and salt resistance, can effectively adsorb heavy metal ions, and exhibits long-term sustained release fertilizer performance in plant fertilizer solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685027A_ABST
    Figure CN119685027A_ABST
Patent Text Reader

Abstract

The invention discloses an environment-friendly material for resisting drought, retaining water, releasing nitrogen and removing cadmium and lead as well as a preparation method and application thereof, and relates to the technical field of soil remediation. The preparation method of the environment-friendly material for resisting drought, retaining water, releasing nitrogen and removing cadmium and lead comprises the following steps: mixing solid waste, diatomite and water for reaction to obtain hydrated calcium silicate; the preparation method comprises the following steps: mixing water and the waste fruit peel powder to obtain a dispersion liquid, heating, preserving heat, cooling, adding an initiator, adding monomer acid, hydrated calcium silicate and a cross-linking agent in an oxygen-free environment, heating, reacting, and filtering to obtain the environment-friendly material. The invention solves the problem of lack of a material capable of repairing heavy metal pollution of soil and ensuring long-acting fertilization of plants at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil remediation, and in particular to an environmentally friendly material capable of resisting drought, retaining water, releasing nitrogen, and removing cadmium and lead, as well as a preparation method and application thereof. Background Art

[0002] Traditional fertilizers face two major problems in the use of agricultural production: first, the amount of fertilizer used is large and the utilization rate is low. The seasonal fertilizer utilization rate in my country is 30-35% for nitrogen fertilizer, 10-25% for phosphorus fertilizer, and 35%-50% for potassium fertilizer. Second, the application of fertilizers is unreasonable. At present, the application of fertilizers in my country is still mainly based on the application of quick-acting fertilizers in batches, with low utilization rate, short fertilizer efficiency cycle, high cost, and environmental pollution.

[0003] Among the soils of different land use types, the soil points in cultivated land had the highest rate of exceeding the standard, at 19.4%. Among them, the heavy metal pollutants mainly include mercury, arsenic, copper, lead, chromium, zinc, and nickel, which seriously polluted agricultural cultivated land and agricultural products, causing the heavy metal residues in agricultural products in these places to exceed the standard, and leading to soil compaction, reduced soil fertility, rampant pests and diseases, and reduced agricultural product yield and quality. How to repair soil heavy metal pollution and ensure sustainable agricultural development is a problem of common concern to the current agricultural and environmental protection communities.

[0004] Hydrated calcium silicate stone is mainly composed of silicate, calcium ions and water molecules. Its structure is complex and exists in many forms, such as calcite, pentetrafluoroethylene, gypsum, etc. Hydrated calcium silicate is widely used in the construction industry, such as for making gypsum boards, gypsum bricks and other building materials, and can also be used for building decoration and maintenance projects. The amount of biomass solid waste generated also increases with the increase in population. In 2019, the global annual production of fruit peel biomass exceeded 144.8 million tons, and the peels are generally discarded as by-products. If hydrated calcium silicate stone and fruit peels can be fully utilized as plant fertilizers and heavy metal adsorption materials, the cost of soil remediation and plant fertilization will be reduced, ensuring the sustainable development of agriculture. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the soil is seriously polluted by heavy metals, and there is a lack of a material that can repair the soil heavy metal pollution while ensuring long-term fertilization for plants. The purpose is to provide an environmentally friendly material that is drought-resistant, water-retaining, nitrogen-releasing, and cadmium-lead-removing, and a preparation method and application thereof, which solves the problem of the lack of a material that can repair the soil heavy metal pollution while ensuring long-term fertilization for plants.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing an environmentally friendly material that resists drought, retains water, releases nitrogen, and removes cadmium and lead, comprising the following steps:

[0008] The solid waste, diatomaceous earth and water are mixed and reacted to obtain hydrated calcium silicate stone;

[0009] Mix water and waste peel powder to obtain a dispersion, heat and keep warm, then cool, add an initiator, add monomer acid, hydrated calcium silicate stone and a cross-linking agent in an anaerobic environment, heat and react, filter, and obtain an environmentally friendly material.

[0010] As a possible design, the solid waste includes at least two of blast furnace slag, incineration slag, red mud and diatomaceous earth.

[0011] Hydrated calcium silicate stone is prepared by the following method:

[0012] The solid waste and diatomaceous earth are mixed to obtain a mixture, the mixture and water are added into a reaction container, reacted at 160-200° C. for 10-14 hours, filtered, washed and then dried to obtain hydrated calcium silicate stone.

[0013] As a possible design, the molar ratio of Ca to Si in the above mixture is 0.78-0.96:1, and the liquid-to-solid ratio of water to the mixture is 18-22 mL / g.

[0014] As a possible design, the above dispersion is heated to 70-80°C, kept warm for 20-40 minutes, and cooled to 45-55°C.

[0015] As a possible design, the initiator is persulfate; the cross-linking agent is sodium vinyl sulfonate, N,N′-methylenebisacrylamide, glutaraldehyde or epichlorohydrin.

[0016] As a possible design, after the monomer acid, hydrated calcium silicate stone and cross-linking agent are added to the dispersion, the temperature is raised to 70-100° C. and the reaction is carried out for 20-40 minutes.

[0017] 7. The method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing environmentally friendly material according to claim 1, the method further comprising:

[0018] The environmentally friendly materials are soaked in a soaking solution, washed, dried and crushed.

[0019] In a second aspect, the present invention provides an environmentally friendly material that resists drought, retains water, releases nitrogen, and removes cadmium and lead, which is prepared by the above-mentioned preparation method.

[0020] In a third aspect, the present invention provides a method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-removing and lead-removing slow-release material, comprising:

[0021] The environmentally friendly material prepared by the above preparation method is soaked in a plant fertilizer solution, and then filtered and dried to obtain a slow-release material.

[0022] In a fourth aspect, the present invention provides the use of the environmentally friendly material prepared by the above preparation method in the preparation of sustained-release materials.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] The present invention reacts a crosslinking agent, peel powder and hydrated calcium silicate stone to obtain a multifunctional material having excellent thermal stability of the three-dimensional structure, overall hydrophilic group content and salt resistance. As an inorganic mineral, hydrated calcium silicate stone can be used as a crosslinking point to increase the overall stability of the material. Because it acts inside the material, it can also increase the concentration difference between the material and the water body, thereby improving the water absorption and retention performance. In addition, the environmentally friendly material to which peel powder and hydrated calcium silicate stone are added contains a significant increase in hydrophilic groups, which improves the material's water retention, fertilizer retention and heavy metal adsorption performance. The results show that in a 400 mg / L solution, the corresponding Cd 2+ and Pb 2+ The adsorption amounts can reach 299.00mg / g and 579.00mg / g respectively.

[0025] The present invention soaks the environmentally friendly material in a urea solution. Since urea is a non-electrolyte fertilizer, there will be no obvious electrostatic repulsion, and the environmentally friendly material can adsorb the urea fertilizer to a large extent; in addition, some urea can also react with the carboxylic acid group on the chain of the environmentally friendly material to generate amide, thereby reducing the electrostatic effect of urea, and the other is converted into a biuret compound and retained on the environmentally friendly material, thereby preparing a high-quality slow-release material. The slow-release material not only has an excellent heavy metal adsorption function, but also can provide a long-acting slow-release fertilizer for plant growth. The slow-release performance of the fertilizer of the slow-release material is less than 1% after 6 days, which proves that its slow-release performance is very excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0027] Figure 1 This is a surface morphology of the waste peel powder (grapefruit peel) used in the present invention;

[0028] Figure 2 This is a surface morphology of the calcium silicate hydrate stone prepared in Example 1 of the present invention;

[0029] Figure 3 This is a surface morphology of the environmentally friendly material prepared in Example 1 of the present invention;

[0030] Figure 4 Thermogravimetric analysis diagrams of the peel powder used in the present invention, the hydrated calcium silicate stone prepared in Example 1, the environmentally friendly material of Comparative Example 2, and the environmentally friendly material of Example 3;

[0031] Figure 5 Infrared analysis diagrams of the peel powder used in the present invention, the hydrated calcium silicate stone prepared in Example 1, the environmentally friendly material in Comparative Example 2, and the environmentally friendly material in Example 3;

[0032] Figure 6 This is a surface morphology of the conventional calcium silicate hydrate stone used in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0034] In a first aspect, the present invention provides a method for preparing an environmentally friendly material that resists drought, retains water, releases nitrogen, and removes cadmium and lead, comprising the following steps:

[0035] S1, mixing solid waste, diatomaceous earth and water to obtain hydrated calcium silicate stone;

[0036] In some embodiments of the present invention, the solid waste includes at least two of blast furnace slag, incineration slag, red mud and diatomaceous earth.

[0037] Preferably, the above-mentioned solid waste includes at least one of blast furnace slag and incineration slag, and also includes at least one of red mud and diatomaceous earth.

[0038] In some embodiments of the present invention, the calcium silicate hydrate is prepared by the following method:

[0039] The solid waste and diatomaceous earth are mixed to obtain a mixture, the mixture and water are added into a reaction container, reacted at 160-200° C. for 10-14 hours, filtered, washed and then dried to obtain hydrated calcium silicate stone.

[0040] Under this condition, c-axis d 002 spacing Hydrated calcium silicate with a layered crystal structure. The layer spacing of this structure is conducive to the embedding, isomorphous substitution and ion exchange of heavy metal ions.

[0041] Preferably, the above-mentioned waste peels include grapefruit peels, lemon peels and / or tangerine peels.

[0042] Preferably, the above-mentioned monomer acid includes but is not limited to monomer acids such as 2-ethylacrylic acid, 4-phenylene acid or acrylic acid.

[0043] Preferably, the reaction pressure is 0.8-1.2 MPa.

[0044] Preferably, the water is deionized water.

[0045] Preferably, the above reaction is carried out in a high pressure reactor, wherein the mixture is autoclaved at 160-200° C. for 10-14 h.

[0046] Preferably, the washing is performed with ultrapure water, and then dried at 80° C. for 12 hours.

[0047] In some embodiments of the present invention, the molar ratio of Ca to Si in the above mixture is 0.78-0.96:1, and the liquid-to-solid ratio of water to the mixture is 18-22 mL / g.

[0048] If the ratio of Ca to Si is not limited to this range, it is difficult to synthesize Hydrated calcium silicate with a layered crystal structure, probably synthesized hydrated calcium silicate stone (and this crystal form cannot effectively exert the above-mentioned performance effects), or hydrated calcium silicate stone cannot be synthesized, because the crystal structure of hydrated calcium silicate stone requires such a large amount of Ca and Si content to be synthesized.

[0049] Preferably, the molar ratio of Al to Si in the above mixture is 0.3 to 0.5:1. The inventors have found that the molar ratio of Al to Si must be within this ratio range to synthesize Hydrated calcium silicate stone with a layered crystal structure.

[0050] S2, water and waste peel powder (refer to Figure 1 ) to obtain a dispersion, heat and keep warm, then cool, add an initiator, add a monomer acid, hydrated calcium silicate stone and a cross-linking agent in an anaerobic environment, heat to react, filter, and obtain an environmentally friendly material.

[0051] By adding water to the waste peel powder and heating it, the waste peel powder can be evenly dispersed in the dispersion. Cooling can prepare for the subsequent addition of the initiator, so that the chain is not easily broken after the initiator is added. After the initiator is added, the oxygen-free environment can provide reaction conditions for the subsequent monomer to produce a chain extension reaction under the crosslinking agent and free radicals.

[0052] Hydrated calcium silicate stone is a hydrophilic layered silicate clay mineral that can be well cross-linked with organic monomers and can act as a cross-linking agent to a certain extent. Together with the cross-linking agent added in the reaction, it affects the cross-linking of the material and helps to form a water-retaining material with hydrated calcium silicate stone particles as the main grid points and a moderate degree of cross-linking, which is beneficial to improving the water absorption and water resistance of environmentally friendly materials.

[0053] Waste peel powder contains numerous hydrophilic groups, which can increase the hydrophilicity of the system. At the same time, since waste peel is rich in cellulose and hemicellulose, cross-linking and blending with hydrated calcium silicate stone is beneficial to the cross-linking and entanglement of the overall system, thereby achieving the stability of the three-dimensional structure and the formation of suitable pores, improving the performance of water absorption and retention, adsorption of heavy metals and slow release and fertilizer retention. Moreover, since orange peel powder is rich in cellulose, hemicellulose, pectin (galacturonic acid) and alkaloids, etc., it can significantly improve the biodegradability and biocompatibility of the original water-retaining material and save costs. In addition, the small and moderate pores of waste peel powder can improve the slow release efficiency of the prepared slow release material.

[0054] Preferably, the addition ratio of the waste peel powder and the monomer acid is 7 to 7.5 g / Mol.

[0055] Preferably, the above-mentioned anaerobic environment can be prepared by introducing nitrogen for 10 minutes before the reaction.

[0056] In some embodiments of the present invention, the dispersion is heated to 70-100°C and kept warm for 20-40 min, and then cooled to 45-55°C.

[0057] In some embodiments of the present invention, the initiator is persulfate; the cross-linking agent is sodium vinyl sulfonate, N,N′-methylenebisacrylamide, glutaraldehyde or epichlorohydrin.

[0058] Preferably, the weight ratio of the persulfate, the waste peel powder, the cross-linking agent and the hydrated calcium silicate stone is (8-12): (8-12): (1-3): (1-7).

[0059] The above-mentioned persulfate includes potassium persulfate, ammonium persulfate or other persulfates.

[0060] Preferably, the concentration of potassium persulfate is 8-12 wt %.

[0061] Preferably, the neutralization degree of the monomer acid is 70-80%.

[0062] Neutralization means using alkaline substances such as sodium hydroxide to neutralize the monomer acid. The monomer acid is a compound with an acidic group, and its aqueous solution is usually acidic. During the polymerization process, if the acidity of the monomer acid is not effectively controlled, it may cause instability in the polymerization reaction and even induce side reactions. By adding sodium hydroxide for neutralization, the pH value of the solution can be adjusted to a suitable range, thereby stabilizing the polymerization system and improving the efficiency and controllability of the polymerization reaction. In addition, the neutralized monomer acid is more likely to undergo polymerization because the alkaline environment helps to reduce the activation energy of the reaction and accelerate the reaction rate. Neutralization can also reduce the occurrence of side reactions and increase the yield and purity of the polymerization reaction. Experiments have shown that a neutralization degree of 70 to 80% is most suitable for rapid synthesis of polymerization reactions.

[0063] In some embodiments of the present invention, after the monomer acid, hydrated calcium silicate stone and cross-linking agent are added to the dispersion, the temperature is raised to 70-100° C. and the reaction is carried out for 20-40 minutes.

[0064] In some embodiments of the present invention, the above preparation method further comprises:

[0065] S3, soaking the environmentally friendly materials with soaking solution, washing, drying and crushing.

[0066] The soaking solution includes anhydrous ethanol, butanol, ethyl acetate or 2-propanol.

[0067] By soaking in solution, washing with water and drying, impurities in environmentally friendly materials can be removed and the subsequent heavy metal adsorption effect can be improved.

[0068] Preferably, the environmentally friendly material is soaked in the soaking solution for 30 to 90 minutes, washed with water for 2 to 4 times, dried and crushed.

[0069] Preferably, the drying temperature is 80°C.

[0070] In a second aspect, the present invention provides an environmentally friendly material that resists drought, retains water, releases nitrogen, and removes cadmium and lead, which is prepared by the above-mentioned preparation method.

[0071] In a third aspect, the present invention provides a method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-removing and lead-removing slow-release material, comprising:

[0072] The environmentally friendly material prepared by the above preparation method is immersed in a plant fertilizer solution, filtered and dried to obtain a slow-release material.

[0073] After research, the inventors found that soaking the environmentally friendly material in a fertilizer solution such as urea will promote the adsorption of heavy metals, because urea, as a derivative of carbonic acid and an amide, has an amide group containing a lone electron pair, which can form a coordination bond with a variety of metal ions.

[0074] Preferably, the above-mentioned plant fertilizer is urea.

[0075] Preferably, the soaking time is 20 to 28 hours.

[0076] In a fourth aspect, the present invention provides the use of the environmentally friendly material prepared by the above preparation method in the preparation of sustained-release materials.

[0077] Example 1

[0078] A method for preparing an environmentally friendly material for resisting drought, retaining water, releasing nitrogen, and removing cadmium and lead, comprising the following steps:

[0079] S1. Add blast furnace slag, red mud, diatomaceous earth and deionized water into a 250 mL autoclave, so that the molar ratio of Ca to Si is 0.85:1, the molar ratio of Al to Si is 0.4:1, and the liquid-solid ratio is 20 mL / g. Then, use an autoclave to autoclave the mixture for 12 hours at 180 ° C, cool, filter and wash with ultrapure water until there is no impurity. Finally, dry the synthesized product in an oven at 80 ° C for 12 hours to obtain hydrated calcium silicate (refer to Figure 2 ).

[0080] S2. Add 60mL of deionized water and 10wt% of grapefruit peel powder (relative to the mass of 0.1M2-ethyl acrylic acid) to a 250mL four-necked flask with mechanical stirring, stir and mix evenly to obtain a dispersion. Subsequently, the temperature is continuously heated to 80°C and maintained for 30 minutes. Then cool to 48°C. Then add 10wt% ammonium persulfate (APS) solution and stir evenly. After N2 is introduced for 10 minutes, a mixed solution of 2-ethyl acrylic acid, epichlorohydrin, and hydrated calcium silicate stone containing 80% neutralization degree is added to the flask, and the temperature is slowly raised to 80°C while stirring. Environmentally friendly materials can be synthesized in about 30 minutes. The weight ratio of the above-mentioned ammonium persulfate, peel powder, epichlorohydrin and hydrated calcium silicate stone is 10:10:2:2.

[0081] S3. Soak the environmentally friendly material in 2-propanol for 0.5 h, and wash it with deionized water 4 times. Cut it into pieces and dry it in a 60°C oven, crush it at room temperature, and pass it through a 40-mesh sieve for later use.

[0082] Example 2

[0083] This embodiment is basically the same as Embodiment 1, except that the weight ratio of the ammonium persulfate, peel powder (grapefruit peel), epichlorohydrin and calcium silicate hydrate is 10:10:4:2.

[0084] Example 3

[0085] This embodiment is basically the same as Embodiment 1, except that the weight ratio of the ammonium persulfate, peel powder (grapefruit peel), epichlorohydrin and calcium silicate hydrate is 10:10:6:2.

[0086] The surface morphology of this environmentally friendly material is shown in Figure 3 shown.

[0087] Comparative Example 1

[0088] This comparative example is substantially the same as Example 1, except that no peel powder and hydrated calcium silicate stone are used.

[0089] Observing the surface morphology of the hydrated calcium silicate stone of Example 1 and the conventional hydrated calcium silicate stone of Comparative Example 1, it can be seen that the microscopic morphology of the two is very different, and the inventors have found that only the c-axis d 002 spacing The layered crystal structure of hydrated calcium silicate stone can achieve excellent heavy metal ion embedding, isomorphous substitution and ion exchange effects.

[0090] Comparative Example 2

[0091] This comparative example is substantially the same as Example 1, except that no hydrated calcium silicate stone is used.

[0092] Comparative Example 3

[0093] This comparative example is basically the same as Example 1, except that calcium silicate hydrate (such as Figure 6 As shown) replaces the hydrated calcium silicate stone prepared by the present invention.

[0094] Experimental Example 1

[0095] (I) The water absorption of the environmentally friendly materials of Examples 1 to 3 and Comparative Examples 1 to 2 was tested. The results are shown in Table 1.

[0096] The water absorption test steps are as follows:

[0097] During the experiment, 0.2g of dry samples of different environmentally friendly materials were weighed and completely immersed in 1L of deionized water at room temperature. The samples were allowed to absorb water and swell for 24 hours until equilibrium was reached. The swollen samples were filtered using a 100-mesh nylon mesh bag and the surface moisture was removed using filter paper before being weighed. The water absorption and swelling experiment was carried out three times in parallel.

[0098] The equilibrium water absorption rate Qeq (g / g) is calculated according to the following formula:

[0099]

[0100] Where W1 and W2 are the masses of the dry and expanded samples, respectively;

[0101] Q eqExpressed as grams of equilibrium water absorption per gram of dry sample.

[0102] Table 1

[0103]

[0104]

[0105] It can be seen from Table 1 that Example 1 has the best water retention performance. By comparing Examples 1 to 3, it can be seen that when the ratio of epichlorohydrin to hydrated calcium silicate stone is 1:1, the water absorption of the environmentally friendly material is the best. By comparing Example 1 and Comparative Examples 1 to 2, it can be seen that both peel powder and hydrated calcium silicate stone are very important for the water absorption of the environmentally friendly material, and the lack of any one of them will lead to a decrease in the water absorption of the environmentally friendly material.

[0106] (ii) The water retention of the environmentally friendly materials of Example 3 and Comparative Examples 1-2 was tested under soil conditions. The results are shown in Table 2.

[0107] The steps for water retention test are as follows:

[0108] The soil water evaporation performance experiment was carried out in clay soil. The experiment was conducted using different environmentally friendly materials. 1g of environmentally friendly materials and 40g of soil samples were added to each 50mL centrifuge tube and mixed evenly. Then 15mL of deionized water was slowly added, weighed with an analytical balance (W1) (accurate to 0.0001g), and control experiments were carried out on different soil samples. The centrifuge tubes were stored at room temperature and weighed every day, recorded as Wi. The water evaporation ratio (We, %) of different soil samples was calculated by the following formula:

[0109]

[0110] Table 2

[0111]

[0112] It can be seen from Table 2 that the lack of peel powder and hydrated calcium silicate stone will lead to a decrease in the water retention performance of the environmentally friendly material.

[0113] (III) The environmentally friendly materials of Examples 1 to 3 and Comparative Examples 1 to 2 were tested for heavy metal adsorption performance under the same conditions. The results are shown in Table 4.

[0114] Heavy metal adsorption test steps:

[0115] In order to explore the versatility of environmentally friendly materials, this experiment also evaluated the adsorption performance and adsorption mechanism of different environmentally friendly materials on cadmium and lead in aqueous solution. In the experiment, 0.02g of environmentally friendly materials were weighed and added to a 50mL centrifuge tube with an initial pH of 5.94, and 40-50mL of different concentrations of Cd 2+ , Pb2+ , and then placed in a shaker at 25°C. Set the shaking time to 24h and the speed to 80rpm until the adsorption is completed. The filtrate was filtered through a 0.45μm filter membrane and tested by ICP-AES. Each sample was tested twice in parallel. Cd(II) and Pb(II) removal rates (η) and adsorption amounts (Q t ) is calculated as follows:

[0116]

[0117] Where C0 is Cd 2+ or Pb 2+ Initial solution concentration, mg / L; C t Cd is the time t 2+ or Pb 2+ Solution concentration, mg / L; m is the mass of the newly added environmentally friendly material, g.

[0118] Table 4

[0119]

[0120] From Table 4, it can be seen that Example 3 has the largest adsorption rate and adsorption amount for Cd and Pb, which indicates that Example 3 has the best adsorption effect.

[0121] (IV) The environmentally friendly materials of Examples 1 to 3 and Comparative Examples 1 to 2 were tested for heavy metal adsorption performance under different concentration conditions. The results are shown in Table 5.

[0122] The steps of the heavy metal adsorption test at different concentrations are as follows:

[0123] Based on the heavy metal adsorption test steps described in (iii), the changes in this experiment are to add 50-400 mg / L solution of Cd(II) or Pb(II), respectively, and add 0.05 (or 0.02) g of sample until adsorption equilibrium (25°C; 80 rpm).

[0124] Table 5

[0125]

[0126]

[0127] It can be seen from Table 5 that when the dosage is low, Example 3 has the best adsorption effect on Cd and Pb. As the dosage increases, the adsorption effects of Comparative Examples 1 to 2 are close to that of Example 3.

[0128] (V) The peel powder used in the present invention, the hydrated calcium silicate stone prepared in Example 1, the environmentally friendly material of Comparative Example 2 (HBM1) and the environmentally friendly material of Example 3 (HBM2) were subjected to thermogravimetric analysis.

[0129] The results are as follows Figure 4 As shown, the thermal decomposition processes of the peel powder (GP), the hydrated calcium silicate stone (HCSS) prepared in Example 1, the environmentally friendly material (HBM1) of Comparative Example 2, and the environmentally friendly material (HBM2) of Example 3 were analyzed by TGA. During the thermal decomposition test, the four samples were tested at a heating rate of 10K / min under a nitrogen atmosphere.

[0130] For the GP sample, its thermal decomposition process went through two stages (marked with pink dotted lines in the figure). The first stage was carried out at a temperature below 150°C, and the mass decreased by 6.41%, which was attributed to the dehydration of attached water. The weight loss in the second stage occurred after 200°C, with a significant weight loss at first and then a slow weight loss process. The weight loss in the second stage reached 63.80%, which corresponds to the degradation of polymers in GP, ​​the defunctionalization and decomposition of cellulose chains, and the release of low molecular weight gases such as CO, CH4, CO2, volatile compounds, and finally the degradation of carbonaceous residues.

[0131] Compared with the GP sample, the thermal decomposition curve of the hydrated calcium silicate stone sample is more gentle. Its thermal decomposition process went through four stages, with weight loss rates of 5.10%, 2.52%, 1.38% and 4.63% respectively. The reasons for the weight loss are attributed to the loss of free water and a small amount of hydrated calcium silicate in the pore structure of the sample, the dehydration of the existing hydrated phase, the loss of crystal water of hydrated calcium silicate stone to form metastable phases such as dehydroxylated hydrated calcium silicate stone, and the further decomposition of the hydrated calcium silicate phase with low crystal water content into a stable wollastonite phase.

[0132] For the HBM1 sample, its thermal decomposition process also went through four stages, namely, weight loss of 11.80% at about 250°C, weight loss of 12.89% at about 250-400°C, weight loss of 31.48% at about 400-500°C, and weight loss of 4.87% at about 500-800°C. The above four stages of thermal decomposition are attributed to the evaporation of water in the sample, the destruction of the oxygen-containing functional groups and carboxyl groups of the polymer side chains, the thermal decomposition of the polymer segments, and the destruction of the overall structure of the hydrogel.

[0133] The thermal decomposition process of HBM2 is similar to that of HBM1 sample. In addition, the residual mass ratio of HBM1 and HBM2 is higher than that of GP, which shows that the thermal stability of HBM composite environmentally friendly materials is improved compared with GP.

[0134] (VII) The peel powder used in the present invention, the hydrated calcium silicate stone prepared in Example 1, the environmentally friendly material in Comparative Example 2 and the environmentally friendly material in Example 3 were subjected to infrared analysis.

[0135] The results are as follows Figure 5As shown, Fig. 5 shows the characterization results of the peel powder (GP), the hydrated calcium silicate stone (HCSS) prepared in Example 1, the environmentally friendly material of Comparative Example 2 (HBM1) and the environmentally friendly material of Example 3 (HBM2), respectively.

[0136] In GP samples, the wavelength is between 3000-3600 cm -1 The broad absorption peak at 2930 cm -1 The sharper absorption peaks belong to the stretching vibration of -OH group and CH group. -1 、1512cm -1 The absorption peaks are attributed to the bending vibration of the -OH group in water and the bending vibration of C=O in the -COO- group. -1 The broad absorption peak can be attributed to the stretching vibration of COC.

[0137] For HCSS samples, the range is 3116-3712 cm -1 The broad absorption peak is due to the stretching vibration of the -OH group, while the peak at 1670 cm -1 The absorption peak at 1440cm -1 The absorption peaks near belong to CO3 2- The asymmetric stretching vibration of -1 and 500cm -1 The absorption peaks nearby are attributed to the stretching vibration of Si-O and the bending vibration of O-Si-O, respectively, and these sites belong to the characteristic absorption peaks of hydrated calcium silicate stone.

[0138] Compared with hydrated calcium silicate, HBM1 has a -1 There are typical stretching vibrations of GP CH groups nearby, as well as a -1 The bending vibration of C=O in the -COO- group indicates the successful synthesis of HBM1.

[0139] Compared with GP and hydrated calcium silicate stone samples, HBM1 and HBM12 composite environmentally friendly materials have a -1 There is a characteristic absorption peak of monomer acid -COO- group nearby, which proves the successful synthesis of HBM composite environmentally friendly materials.

[0140] Example 4

[0141] A method for preparing an environmentally friendly material for resisting drought, retaining water, releasing nitrogen, and removing cadmium and lead, comprising the following steps:

[0142] S1. Add blast furnace slag, red mud, diatomaceous earth and deionized water to a 250 mL autoclave, so that the molar ratio of Ca to Si is 0.8:1, the molar ratio of Al to Si is 0.3:1, and the liquid-solid ratio is 18 mL / g. Then, use an autoclave to autoclave the mixture for 10 hours at 160 ° C, cool, filter and wash with ultrapure water until there is no impurity. Finally, the synthesized product is dried in an oven at 80 ° C for 12 hours to obtain hydrated calcium silicate stone.

[0143] S2. Add 60mL of deionized water and 10wt% of peel powder (lemon peel, relative to the mass of 0.1M 4-phenylene acid) to a 250mL four-necked flask with mechanical stirring, stir and mix evenly to obtain a dispersion. Subsequently, the temperature is continuously heated to 70°C and maintained for 20 minutes. Then cool to 45°C. Then add 8wt% ammonium persulfate solution and stir evenly. After N2 is introduced for 10 minutes, a mixed solution of 4-phenylene acid, epichlorohydrin, and hydrated calcium silicate stone containing 80% neutralization degree is added to the flask, and the temperature is slowly raised to 70°C while stirring. Environmentally friendly materials can be synthesized in about 20 minutes, and the weight ratio of the above-mentioned ammonium persulfate, peel powder, epichlorohydrin and hydrated calcium silicate stone is 10:10:2:2.

[0144] S3. Soak the environmentally friendly material in anhydrous ethanol for 30 minutes, wash it twice with deionized water, cut it into pieces and dry it in a 60℃ oven, crush it at room temperature, pass it through a 40-mesh sieve and store it for later use.

[0145] Example 5

[0146] A method for preparing an environmentally friendly material for resisting drought, retaining water, releasing nitrogen, and removing cadmium and lead, comprising the following steps:

[0147] S1. Add blast furnace slag, red mud, diatomaceous earth and deionized water into a 250 mL autoclave, so that the molar ratio of Ca to Si is 0.88:1, the molar ratio of Al to Si is 0.45:1, and the liquid-solid ratio is 21 mL / g. Then, the mixture is autoclaved at 190 ° C for 12 hours using an autoclave, cooled, filtered and washed with ultrapure water until free of impurities. Finally, the synthesized product is dried in an oven at 80 ° C for 12 hours to obtain hydrated calcium silicate stone.

[0148] S2. Add 60mL of deionized water and 10wt% of peel powder (relative to the mass of 0.1M 4-phenylene acid) to a 250mL four-necked flask with mechanical stirring, stir and mix evenly to obtain a dispersion. Subsequently, the temperature is continuously heated to 70-80°C and maintained for 30 minutes. Then cool to 50°C. Then add 11wt% ammonium persulfate solution and stir evenly. After passing N2 for 10 minutes, add a mixed solution of 4-phenylene acid, epichlorohydrin, and hydrated calcium silicate stone containing a neutralization degree of 70-80% to the flask, and slowly heat to 78°C while stirring. Environmentally friendly materials can be synthesized in about 40 minutes. The weight ratio of the above-mentioned ammonium persulfate, peel powder, epichlorohydrin and hydrated calcium silicate stone is 10:10:4:2.

[0149] S3. Soak the environmentally friendly material in anhydrous ethanol for 90 minutes, and wash it with deionized water for 4 times. Cut it into pieces and dry it in a 60℃ oven, crush it at room temperature, and pass it through a 40-mesh sieve for later use.

[0150] Example 6

[0151] A method for preparing an environmentally friendly material for resisting drought, retaining water, releasing nitrogen, and removing cadmium and lead, comprising the following steps:

[0152] S1. Add blast furnace slag, red mud, diatomaceous earth and deionized water into a 250 mL autoclave, so that the molar ratio of Ca to Si is 0.9:1, the molar ratio of Al to Si is 0.5:1, and the liquid-solid ratio is 22 mL / g. Then, use an autoclave to autoclave the mixture for 14 hours at 200 ° C, cool, filter and wash with ultrapure water until there is no impurity. Finally, the synthesized product is dried in an oven at 80 ° C for 12 hours to obtain hydrated calcium silicate stone.

[0153] S2. Add 60mL of deionized water and 10wt% of peel powder (relative to the mass of 0.1M 4-phenylene acid) to a 250mL four-necked flask with mechanical stirring, stir and mix evenly to obtain a dispersion. Subsequently, the temperature is continuously heated to 80°C and maintained for 40 minutes. Then cool to 55°C. Then add 12wt% ammonium persulfate solution and stir evenly. After passing N2 for 10 minutes, add a mixed solution of 4-phenylene acid, epichlorohydrin, and hydrated calcium silicate stone containing 80% neutralization degree to the flask, and slowly heat to 80°C while stirring. Environmentally friendly materials can be synthesized in about 40 minutes. The weight ratio of the above-mentioned ammonium persulfate, peel powder, epichlorohydrin and hydrated calcium silicate stone is 10:10:6:2.

[0154] S3. Soak the environmentally friendly material in anhydrous ethanol for 90 minutes, and wash it with deionized water for 4 times. Cut it into pieces and dry it in a 60℃ oven, crush it at room temperature, and pass it through a 40-mesh sieve for later use.

[0155] Example 7

[0156] A method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing slow-release material comprises the following steps:

[0157] The environmentally friendly material prepared in Example 1 was immersed in a urea solution of a selected concentration for 24 hours, and then filtered and placed in a constant temperature drying oven at 80° C. for drying for later use.

[0158] Example 8

[0159] A method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing slow-release material comprises the following steps:

[0160] The environmentally friendly material prepared in Example 3 was immersed in a urea solution of a selected concentration for 24 hours, and then filtered and placed in a constant temperature drying oven at 80° C. for drying for later use.

[0161] Comparative Example 4

[0162] This comparative example is basically the same as Example 6, except that: no peel powder and hydrated calcium silicate stone are used in the environmentally friendly material.

[0163] Comparative Example 5

[0164] This comparative example is basically the same as Example 6, except that no hydrated calcium silicate stone is used in the environmentally friendly material.

[0165] Experimental Example 2

[0166] The sustained-release materials of Example 6 and Comparative Examples 4-5 were tested for fertilizer retention in water. The results are shown in Table 3.

[0167] The steps of urea slow-release test are as follows:

[0168] In the urea release study, 0.1g of sustained-release material (containing 0.141g of urea) was soaked in a beaker with 100mL of sterile deionized water and gently stirred. 1mL of solution was collected at regular intervals to determine the urea concentration, and 1mL of sterile water was added to the beaker to keep the solution constant. According to the urea calibration curve, the urea concentration in the sample was determined by colorimetry. The urea release ratio was calculated according to the following formula:

[0169]

[0170] Where M t M0 and M1 respectively represent the mass of urea released by the composite environmentally friendly material at time t and the total mass of urea loaded on the composite environmentally friendly material.

[0171] Table 3

[0172]

[0173] It can be seen from Table 3 that, compared with Comparative Examples 1 to 2, the urea release rate of Example 3 is slower, which is more in line with the absorption rate of fertilizers by plants and has better fertilizer retention performance.

[0174] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an environmentally friendly material for drought resistance, water retention, nitrogen release and cadmium and lead removal, characterized in that: The steps include: The solid waste, diatomaceous earth and water are mixed and reacted to obtain hydrated calcium silicate stone; Mix water and waste peel powder to obtain a dispersion, heat and keep warm, then cool, add an initiator, add monomer acid, hydrated calcium silicate stone and a cross-linking agent in an anaerobic environment, heat and react, filter, and obtain an environmentally friendly material.

2. The method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing environmentally friendly material according to claim 1, characterized in that: The solid waste includes at least two of blast furnace slag, incineration slag, red mud and diatomaceous earth; The calcium silicate hydrate is prepared by the following method: The solid waste and diatomaceous earth are mixed to obtain a mixture, the mixture and water are added into a reaction container, reacted at 160-200° C. for 10-14 hours, filtered, washed and then dried to obtain hydrated calcium silicate stone.

3. The method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing environmentally friendly material according to claim 2, characterized in that: The molar ratio of Ca to Si in the mixture is 0.78 to 0.96:1, and the liquid-to-solid ratio of water to the mixture is 18 to 22 mL / g.

4. The method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing environmentally friendly material according to claim 1, characterized in that: The dispersion is heated to 70-80°C and kept warm for 20-40 minutes, and then cooled to 45-55°C.

5. The method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing environmentally friendly material according to claim 1, characterized in that: The initiator is persulfate; the cross-linking agent is sodium vinyl sulfonate, N,N'-methylenebisacrylamide, glutaraldehyde or epichlorohydrin.

6. The method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing environmentally friendly material according to claim 1, characterized in that: After the monomer acid, hydrated calcium silicate stone and cross-linking agent are added into the dispersion, the temperature is raised to 70-100° C. and the reaction is carried out for 20-40 minutes.

7. The method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing environmentally friendly material according to claim 1, characterized in that: The preparation method further comprises: The environmentally friendly materials are soaked in a soaking solution, washed, dried and crushed; The soaking solution includes anhydrous ethanol, butanol, ethyl acetate or 2-propanol.

8. An environmentally friendly material that resists drought, retains water, releases nitrogen, removes cadmium and lead, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.

9. A method for preparing a drought-resistant, water-retaining, nitrogen-releasing, cadmium-lead-removing slow-release material, characterized in that: include: The environmentally friendly material prepared by the preparation method according to any one of claims 1 to 7 is soaked in a plant fertilizer solution, and then filtered and dried to obtain a slow-release material.

10. Use of the environmentally friendly material prepared by the preparation method according to any one of claims 1 to 7 in the preparation of sustained-release materials.